Case report: Diffuse large B-cell lymphoma presenting as congestive heart failure in a cat - Johnson, Jake; Melhorn, Hannah; Karchemskiy, Sonya; Karlin, Emily; Bain, Perry; Rush, John; Peterson, Cornelia (Frontiers in Veterinary Science, 2024)
Cardiac lymphoma is uncommon in cats and is rarely considered as a differential diagnosis for congestive heart failure. A 10-year-old neutered male domestic short-haired cat with clinical histories of feline immunodeficiency virus, diabetes mellitus, and congestive heart failure was humanely euthanized. Post-mortem evaluation demonstrated a massively infiltrative round cell neoplasm of the heart, resulting in CHF. Immunohistochemistry of neoplastic tissue was consistent with diffuse large B-cell lymphoma. This case demonstrates a peculiar presentation of cardiac diffuse large B-cell lymphoma, with chronic feline lentiviral infection possibly contributing to disease initiation and progression.